Metabolic Consequences after Urinary Diversion - Stein, Raimund; Rubenwolf, Peter (Frontiers in Pediatrics, 2014)
Metabolic disturbances are well-known, but sometimes neglected immediate consequences or late sequelae following urinary diversion (UD) using bowel segments. Whereas subclinical disturbances appear to be quite common, clinically relevant metabolic complications, however, are rare. Exclusion of bowel segments for UD results in loss of absorptive surface for its physiological function. Previous studies demonstrated that at least some of the absorbtive and secreting properties of the bowel are preserved when exposed to urine. For each bowel segment typical consequences and complications have been reported. The use of ileal and/or colonic segments may result in hyperchloremic metabolic acidosis which can be prevented if prophylactic treatment with alkali supplementation is started early. The resection of ileal segments may be responsible for malabsorption of vitamin B12 and bile acids with subsequent neurological and hematological late sequelae as well as potential worsening of the patient’s bowel habits. Hence, careful patient and procedure selection, meticulous long-term follow-up and prophylactic treatment of subclinical acidosis is of paramount importance in the prevention of true metabolic complications.